IMPROVING PUBLIC SALT QUALITY BY CHEMICAL TREATMENT - Diyono Ihsan; Istadi; Mohamed Djaeni (JOURNAL OF COASTAL DEVELOPMENT, 2002)
The public salt produced by salt farmers in Juwana, Pat,i Central Java, Indonesia with the NaCl content of about 92.86% (dry base) is still below the standard quality of industrial salt (98.5% of dry base). Improving public salt quality has become an important topic of discussion. This research look into the influences of chemical compound, namely sodium hydroxide (NaOH), sodium carbonate (Na2CO3) and barium chloride (BaCl2) to reduce pollutant ion (Ca2+, Mg2+ and SO42-) in order to increase the percentage of NaCl content in public salt. The purification process was carried out in three series mixer. In this investigation, 100 ml of public salt solution is gradually treated by adding those compounds, which were varied from 0.50 to 3.50 gram with the step size of 0.50 gram. The results showed that the purity of NaCl could be enhanced up to 99.6% that was achieved by adding 2.00 gram o f NaOH, 1.50 gram of Na2CO3 and 2.50 gram of BaCl2. This purity is suitable to meet community and industrial demands